2018
DOI: 10.1111/codi.14051
|View full text |Cite
|
Sign up to set email alerts
|

The impact of robotic surgery on quality of life, urinary and sexual function following total mesorectal excision for rectal cancer: a propensity score‐matched analysis with laparoscopic surgery

Abstract: The robotic approach for TME was associated with less impairment of urinary and sexual function; QoL was comparable to the laparoscopic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 34 publications
(60 reference statements)
8
109
0
Order By: Relevance
“…The postoperative scores were comparable with preoperative scores at 6 months in the robotic group and at 12 months in the laparoscopic group. Of 48 sexually active men in each group, erectile function scores decreased postoperatively, returning to preoperative levels at 6 months in the robotic group and at 12 months in the laparoscopic groups . Robotic TME in patients with rectal cancer is associated with a lower rate of conversion and lower incidence of urinary retention compared with laparoscopic TME.…”
Section: Arguments For (Khan Banerjee Kim)mentioning
confidence: 86%
“…The postoperative scores were comparable with preoperative scores at 6 months in the robotic group and at 12 months in the laparoscopic group. Of 48 sexually active men in each group, erectile function scores decreased postoperatively, returning to preoperative levels at 6 months in the robotic group and at 12 months in the laparoscopic groups . Robotic TME in patients with rectal cancer is associated with a lower rate of conversion and lower incidence of urinary retention compared with laparoscopic TME.…”
Section: Arguments For (Khan Banerjee Kim)mentioning
confidence: 86%
“…Several studies have assessed urinary and sexual function after RALS and CLS using the International Prostate Symptom Score (IPSS) and the International Index of Erectile Function questionnaire (Table ) . Some of these studies showed significantly improved urinary continence at 3, 6, and 12 months after TME performed by RALS.…”
Section: Urogenital Functionmentioning
confidence: 99%
“…Sexual function returned to baseline at 6 months in the robotic group, but did not return to baseline until 12 months after surgery in the laparoscopic group. Overall, this study showed that although quality of life worsens initially after surgery, the robotic group had an earlier return to baseline quality of life than the laparoscopic group [35] .…”
Section: Robotic Surgery For Rectal Cancermentioning
confidence: 64%
“…Furthermore, several small single center short term studies demonstrated a significant improvement in sexual function. One study even showed a modest improvement in bladder function in robotic surgery patients compared to laparoscopic surgery patients [29][30][31][32][33][34][35][36] . Benefits have been attributed to the superior dissection allowed by robotic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation